Close-In Substellar Companions and the Formation of sdB-Type Close Binary Stars - L. Y. Zhu; S. B. Qian; E.-G. Zhao; E. Fernández Lajús; Z.-T. Han (Acta Polytechnica CTU Proceedings, 2015)
The sdB-type close binaries are believed to have experienced a common-envelope phase and may evolve into cataclysmic binaries (CVs). About 10% of all known sdB binaries are eclipsing binaries consisting of very hot subdwarf primaries and low-mass companions with short orbital periods. The eclipse profiles of these systems are very narrow and deep, which benefits the determination of high precise eclipsing times and makes the detection of small and close-in tertiary bodies possible. Since 2006 we have monitored some sdB-type eclipsing binaries to search for the close-in substellar companions by analyzing the light travel time effect. Here some progresses of the program are reviewed and the formation of sdB-type binary is discussed.